Shaping Sustainable Intensive Production Systems - Improved Crops and Cropping Systems in the Developing World - Stirling, Clare M.; Hellin, Jonathan; Cairns, Jill E.; Silverblatt-Buser E; Tefera, T.; Ngugi H; Gbegbelegbe, Sika; Tesfaye Fantaye, Kindie; Chung, U.; Sonder, Kai; Cox, R.A.; Verhulst, Nele; et al. (CAB International, 2014)
This chapter focuses on the impacts of climate change on intensive maize and wheat production systems. Some technologies to close the yield gap to achieve sustainable intensification are also discussed.